Bibliometric Analysis of Social Support for Children's Mental Health in the Perspective of Islamic Education - Fahmi Arfan; Muhammad Raffa; Indra Nurhadi (Bulletin of Islamic Research, 2023)
This study aims to find out about social support for children's mental health in the perspective of Islamic education in publications indexed by the Scopus database. This study uses bibliometric analysis techniques to explore all publications indexed in the scopus database on social support for children's mental health in the perspective of Islamic education from 1976 to 2023. The data obtained by the analysis used excel and R/R studio. VOSviewer is used to perform a visual analysis of the appearance of keywords and document citations in a stimulating manner. The researchers found 569 publications that corresponded to the subject's function and the criteria set. The results of this study show an annual growth rate of 8.2% with the most publications in 2020. Iran is the country that contributes the most publications with the Iranian Ministry of Health and Medical Education affiliated. The bibliometric analysis carried out was limited to scopus data. Other national and international databases were not taken into account in this research. This study presents a brief overview of the literature accessible to researchers working in the fields of education and psychology and provides recommendations for future research.